POPULATION DYNAMICS OF EUXESTA SPP. (DIPTERA: OTITIDAE) IN MAIZE (Zea Mays L.), WHEAT (Triticum aestivum L.) AND POLYCULTURE - AMANCIO, MARIANA BONIFÁCIO; CRUZ, IVAN (International Journal of Maize & Sorghum, 2020)
In Brazil there is a great concern about the incidence of insect pests on reproductive organs of plants. In maize, there has been some species of Euxesta (Diptera: Otitidae) flies causing damage, especially in sweet maize. The objective of this study was to evaluate the presence of Euxesta spp. in maize, wheat and polyculture. For this, two experiments were carried out in a savanna area. The first was set in two potential hosts, the high protein white maize and the wheat, the second experiment was carried out in a polyculture system (maize, soybean, sorghum and cotton). The insects were captured weekly until the end of cultivation through McPhail traps with hydrolyzed maize protein randomly distributed in both fields..Two species, Euxesta eluta and Euxesta mazorca, were sampled. There was a greater collection of individuals in maize compared to wheat. Higher number of E. eluta was observed in soybean and cotton, followed by maize 1 and 2 and sorghum. The number of E. maize was found to be higher in the two kinds of maize, soybean, cotton and sorghum. The number of females was higher than males in both crops.